Digital transition in facility management. ﻿BIM, CMMS and diagnostic maintenance - Mario Claudio Dejaco; Chiara Scanagatta; Antonino Mannino; Massimiliano Condotta (Agathón)
Managing a building’s life cycle is a fundamental part of designing sustainable constructions and implementing efficient management strategies. The research described in this paper is inserted within this context, with the objective of integrating the facility management phase within this virtuous process. The purpose of the study is to develop a user-friendly and cost-effective strategy that can be used to create a digital twin, based on CMMS, on which to integrate real-time data in order to optimise the use and maintenance phases, moving towards a predictive system. The strategy was developed through two case studies. The first was linked to the procedure to build the digital twin on the CMMS database, and the second was to define the indicators necessary to collect data in real-time, a function underpinning diagnostic maintenance.